Philosophy of education in Philippine setting - Gregorio, Herman C.; Gregorio, Cornelia M. (Quezon City, Philippines : Garotech Publishing, 1979)
The aim of this manuscript is to provide the prospective student of education with the basic philosophic understanding which will enable him or her to arrive at a logical and systematic theory of education. The present volume has been prepared in order to present in a handy form the different schools of educational philosophy as implemented in education in the Philippine setting.
Chapter I. Philosophy and Education -- Chapter II. Metaphysics, Epistemology, and their educational implications -- Chapter III. Different Educational philosophies -- Chapter IV. Educational philosophy of John Dewey -- Chapter V. Dewey's educational philosophy as applied in Philippine settings -- Chapter VI. The Child-centered philosophy of education -- Chapter VII. Democracy as a way of life -- Chapter VIII. Democracy as a way of life -- Chapter IX. Filipino philosophy of education -- Chapter X. Educational philosophy of the new society -- Chapter XI. New philosophical approach in Philippine education -- Chapter XII. Educational concepts based on different schools of philosophy.
Includes index.